2017
DOI: 10.1111/nep.13014
|View full text |Cite
|
Sign up to set email alerts
|

The use of bone turnover markers in chronic kidney disease‐mineral and bone disorders

Abstract: ABSTRACT:Bone turnover markers assist in fracture risk prediction, management and monitoring of osteoporosis in patients without chronic kidney disease (CKD). The use in CKD-mineral bone disorder (MBD) has been limited as many of these markers and breakdown products are renally excreted, including the most commonly used and well standardized procollagen type I N propeptide and C-terminal cross-linking telopeptide of type I collagen. Of the markers unaffected by renal function, bone specific alkaline phosphatas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 21 publications
0
24
0
2
Order By: Relevance
“…In CKD patients, CKD-MBD caused by high or low bone turnover disease impaired the normal bone remodeling process. In high bone turnover diseases, secondary hyperparathyroidism activates receptor activator of nuclear factor kappa-Β ligand (RANKL) signaling as well as osteoclast activity to increase bone resorption [80]. In low bone turnover diseases, inert osteoblast activity decreases the utility of calcium and phosphate, and subsequently decreases the extraosseous calcium-phosphate deposits [81].…”
Section: Introductionmentioning
confidence: 99%
“…In CKD patients, CKD-MBD caused by high or low bone turnover disease impaired the normal bone remodeling process. In high bone turnover diseases, secondary hyperparathyroidism activates receptor activator of nuclear factor kappa-Β ligand (RANKL) signaling as well as osteoclast activity to increase bone resorption [80]. In low bone turnover diseases, inert osteoblast activity decreases the utility of calcium and phosphate, and subsequently decreases the extraosseous calcium-phosphate deposits [81].…”
Section: Introductionmentioning
confidence: 99%
“…However, the recently revised 2017 KDIGO CKD-MBD guidelines recommend monitoring total or bone-specific serum AP activity in patients with advanced CKD [ 2 ]. Although bone formation rate was better correlated with plasma bone-specific AP levels than with either plasma total AP or intact PTH concentrations [ 13 , 14 ], serum total AP was used because of its feasibility for routine monitoring in patients on MHD. A large cohort study showed that increased serum total AP > 120 U/L was associated with mortality among patients on MHD [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…The combination of osteocalcin (<41 ng/L) and BSALP (<23 U/L) improved the positive predictive value for diagnosing adynamic bone disease to 77% in a CKD-5 cohort. [66]…”
Section: Clinical Utility Of Btmsmentioning
confidence: 99%